Cardiopulmonary Safety of Propofol Versus Midazolam/Meperidine Sedation for Colonoscopy: A Prospective, Randomized, Double-Blinded Study - Gurbulak, Bunyamin (Iran Red Crescent Med J, 2014)
BACKGROUND: Different levels of pharmacological sedation ranging from minimal to general anesthesia are often used to increase patient tolerance for a successful colonoscopy. However, sedation increases the risk of respiratory depression and cardiovascular complications during colonoscopy. OBJECTIVES: We aimed to compare the propofol and midazolam/meperidine sedation methods for colonoscopy procedures with respect to cardiopulmonary safety, procedure-related times, and patient satisfaction. PATIENTS AND METHODS: This was a prospective, randomized, double-blinded study, in which 124 consecutive patients undergoing elective outpatient diagnostic colonoscopies were divided into propofol and midazolam/meperidine sedation groups (n: 62, m/f ratio: 26/36, mean age: 46 ± 15 for the propofol group; n: 62, m/f ratio: 28/34, mean age: 49 ± 15 for the midazolam/meperidine group) by computer-generated randomization. The frequency of cardiopulmonary events (hypotension, bradycardia, hypoxemia), procedure-related times (duration of colonoscopy, time to cecal intubation, time to ileal intubation, awakening time, and time to hospital discharge) and patients’ evaluation results (pain assessment, quality of sedation, and recollection of procedure) were compared between the groups. RESULTS: There were no statistically significant differences between the two groups with respect to demographic and clinical characteristics of the patients, the frequency of hypotension, hypoxemia or bradycardia, cecal and ileal intubation times, and the duration of colonoscopy. The logistic regression analysis indicated that the development of cardiopulmonary events was not associated with the sedative agent used or the characteristics of the patients. The time required for the patient to be fully awake and the time to hospital discharge was significantly longer in the propofol group (11 ± 8 and 37 ± 11 minutes, respectively) than the midazolam/meperidine group (8 ± 6 and 29 ± 12 minutes, respectively) (P = 0.009 and P < 0.001, respectively). The patient satisfaction rates were not significantly different between the groups; however, patients in the propofol group experienced more pain than patients in the midazolam/meperidine group (VAS score: 0.31 ± 0.76 vs. 0 ± 0; P = 0.002). CONCLUSIONS: Midazolam/meperidine and propofol sedation for colonoscopy have similar cardiopulmonary safety profiles and patient satisfaction levels. Midazolam/meperidine can be preferred to propofol sedation due to a shorter hospital length of stay and better analgesic activity.